Relationships among patient activation, social support and online health information seeking of community‐dwelling older adults living with coronary heart disease. (2nd September 2022) - Zhu, Yaru; Song, Yuting; Wang, Yinuo; Ji, Heqian; Wang, Derong; Cai, Shuo; Wang, Aimin
Abstract: Aims: To explore the relationship between patient activation (subjective initiative of patients to participate in disease management in self‐health care), social support, self‐efficacy and online health information seeking among older patients with coronary heart disease. Design: A cross‐sectional and survey‐based design. Methods: A total of 451 older patients with coronary heart disease were recruited from July to November 2021 from four communities in Qingdao, China. We collected data using the Patient Activation Measure, Social Support Rating Scale, Self‐Efficacy Scale and Online Health Information Seeking Scale. We performed structural equation modelling to analyse the data. Results: The final model showed good model fit. Patient activation influenced online health information seeking directly ( β  = .39, p  < .05) and indirectly through self‐efficacy ( β  = .17, p  < .05). Social support influenced online health information seeking directly ( β  = .23, p  < .05) and indirectly through self‐efficacy ( β  = .03, p  < .05). Self‐efficacy directly influenced online health information seeking ( β  = .26, p  < .05). Conclusions: We identified the interrelationships of patient activation, social support and self‐efficacy and their influence on the online health information seeking of older patients with coronary heart disease. Our findings provide a theoretical basis for developing and evaluating interventions to enhance online health information seeking for older patients with coronary heart disease. Impact: These findings add a better understanding of the relationship between patient activation, social support, self‐efficacy and online health information seeking in older patients with coronary heart disease, and help community health workers to intervene in the early stage of disease diagnosis.